OPTIMASI RENDEMEN EKSTRAKSI LESITIN DARI MINYAK KEDELAI VARIETAS ANJASMORO DENGAN WATER DEGUMMING [Yield Optimization of Lecithin Extraction of Anjasmoro Variety Soybean Oil by Water Degumming] - Teti Estiasih; Kgs. Ahmadi; Erliana Ginting; Deny Kurniawati (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2013)
Lecithin is one of natural emulsifiers widely used in food industries. The main source of lecithin is soybean and it is obtained during water degumming in soybean oil purification. This research was aimed to optimize the yield of lecithin during water degumming of Anjasmoro variety soybean oil by response surface methodology. The factors optimized were added water (%), temperature (ºC), and extraction time (minute). The relationship between lecithin yield and the parameters was quadratic. The response increased up to a certain point, and then decreased. Optimum water degumming was obtained at water additon of 2.95%, temperature of 61.96°C, and extraction time of 30.02 minutes. At optimum condition, the lecithin yield was 1.55% and the phosphor content was 3865.30 ppm suggesting lecithin purity of 56.24%. Verification showed that the yield was close to the prediction value of 1.49%. The purification process resulted in lecithin purity of 83.96% which was in compliance with the legal purity specification of food grade lecithin.